Sweden Against Apartheid: A Historical Overview - Anna-Mart van Wyk (The Thinker)
Sweden’s relations with the South African liberation movements date back to the 1960s, when the Swedish anti-apartheid movement arose. In addition to moral support and about $400 million dollars in financial support, Sweden became the first Western country to give official political support to the anti-apartheid movement. Such was the relationship between the African National Congress (ANC) and Sweden, that the latter became the first country outside of Africa to be visited by Nelson Mandela in 1990, after his release from decades of imprisonment. The aim of this contribution is therefore to provide a brief synopsis of the rich history of Sweden’s solidarity with the South African liberation struggle and the role played by the Swedish youth, the Swedish antiapartheid movement, civil society, trade unions, and Olof Palme, former Swedish prime minister, who was one of the most committed allies of the liberation movements.